Selection of keystone species based on stable carbon and nitrogen isotopes to construct a typical food web on the shore of Xingkai Lake, China - Minyan Xing (Elsevier, 2021)
Considering the constraint of cost in conserving biodiversity, conservation resources need to be primarily allocated to keystone species. The structure and interaction of strength of the food web determine the stability of the network, and the keystone species is key node for the stable food web. In this research, starting with constructing a diet proportion food web structure model on the shore of Xingkai Lake quantitatively based on carbon and nitrogen stable isotopes. We calculated the feeding ratio between species and used it as the link weight, combined with the complex network centrality theory. Afterwards, we identified the keystone species in the diet proportion food web by calculating the degree centrality, closeness centrality, betweenness centrality and PageRank centrality of each node in the network. We have found that the link weight is the key factor affecting the identification of keystone species. Besides, Chinese white prawn has been identified as the keystone species in the typical food web of the shore of Xingkai Lake shown from the perspective of the food web structure and the results of the four centrality indices. This article is of great significance to identify the keystone species in the food web from a holistic perspective quantitatively, further clarify the conservation goals, and reduce conservation costs under the impact of the global COVID-19 epidemic, so as to conserve biodiversity accurately and effectively.